Effect of Biofeedback Therapy in Constipation According to Rectal Sensation - Ahn, Ji Yong (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Pancreatobiliary Association; Korean Society of Gastrointestinal Cancer, 2013)
BACKGROUND/AIMS: The pathophysiologic mechanism of rectal hyposensitivity (RH) is not well documented, and the significance of RH in biofeedback therapy (BFT) has not been evaluated. Thus, we aimed to assess the effect of BFT in constipated patients according to the presence of RH. METHODS: Five hundred and ninety constipated patients (238 males and 352 females) underwent anorectal physiologic assessments. Of these, anorectal manometry was performed before and after BFT in 244 patients (63 RH and 181 non-RH patients). RESULTS: The success rate of BFT was 56% in the RH and 61% in the non-RH group (p=0.604). The measurements of resting pressure, squeezing pressure, desire to defecate volume, urge to defecate volume, and maximum volume were decreased after BFT in the RH group (p<0.05), whereas only resting and squeezing pressures were decreased in the non-RH group (p<0.05). Among the RH group, individuals who responded to BFT showed decreased resting pressure, squeezing pressure, desire to defecate, urge to defecate, and maximum volume and increased balloon expulsion rate; among those who did not respond to BFT, only desire to defecate volume was improved. CONCLUSIONS: In constipated patients with RH, changes of anorectal manometric findings differed in comparison to patients without RH. The responses to BFT showed both anorectal muscle relaxation and restoration of rectal sensation.